2021
DOI: 10.1021/acssuschemeng.1c04725
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Lignin with Decreased Heterogeneity: Based on a Detailed Characteristics Study of Sequentially Extracted Softwood Kraft Lignin

Abstract: Industrial lignin fractionation is attracting increasing interest due to its enormous potential in the development of high value-added materials. However, the widely reported fractionation approaches are primarily focused on the separation of fractions with a low polydispersity index (PDI). In this study, based on the detailed characteristic examination of carefully sequential-extracted softwood Kraft lignin fractions, a novel method to isolate lignin fraction with decreased heterogeneity (LGF-dh), was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…It is well recognized that solvent fractionation strategies applied to kraft lignins are able to reduce the intrinsic heterogeneity in terms of molecular weight distribution 23 and also refine some structural chemical features 24 either functional groups (such as alcohols, 25 phenols, carboxylic acids) or structural intermonomeric motifs. 26 The recently developed selective derivatization with dansyl chloride of lignin phenolic functionalities coupled with GPC-FL 19 was used in this work to focus the investigation on this important chemical group in lignin, and verify that solvent fractionation permitted not only to obtain fractions more or less rich in phenols but those fractions were also more homogeneous in terms of phenol distribution and molecular weight distribution.…”
Section: Structural Interpretation Of Phenol Distributions In Molecul...mentioning
confidence: 99%
“…It is well recognized that solvent fractionation strategies applied to kraft lignins are able to reduce the intrinsic heterogeneity in terms of molecular weight distribution 23 and also refine some structural chemical features 24 either functional groups (such as alcohols, 25 phenols, carboxylic acids) or structural intermonomeric motifs. 26 The recently developed selective derivatization with dansyl chloride of lignin phenolic functionalities coupled with GPC-FL 19 was used in this work to focus the investigation on this important chemical group in lignin, and verify that solvent fractionation permitted not only to obtain fractions more or less rich in phenols but those fractions were also more homogeneous in terms of phenol distribution and molecular weight distribution.…”
Section: Structural Interpretation Of Phenol Distributions In Molecul...mentioning
confidence: 99%
“…DMK has been confirmed to be an excellent solvent to selectively extract abundant amounts of fractions with a trace amount of carbohydrates both in previous reports as well as in this study. ,, Since DMK could extract 67% of the lignin fraction with a trace amount of carbohydrates by single solvent extraction, we therefore chose DMK to separate the prepurified lignin into two parts: acetone-soluble with a trace amount carbohydrates (LG-TC0) and acetone-insoluble with large amounts of carbohydrates (LG-LC0), as shown in Figure . In a previous study, we demonstrated that lignin fractions with increasing Mw could be obtained by the solvent sequence of EtOAc, EtOH, MeOH, acetone, and dioxane. Moreover, the carbohydrate signals were detected from the fraction extracted by EtOH, MeOH, and dioxane.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, sequential solvent extraction, which uses solvents with different solvent parameters to extract lignin by the precipitation of redissolved lignin in a gradient manner, has been proven an effective strategy to obtain more homogeneous lignin samples. Up to date, solvent sequences, for instance, DCM → MeOH, DCM → isopropanol → MeOH → mixture of MeOH/DCM, ethyl acetate → isopropanol → EtOH → MeOH → actone, , and isopropanol → EtOH → MeOH, have been used to decrease the heterogeneity of lignin. And, the existence of carbohydrates in fractions extracted by isopropanol, EtOH, and MeOH has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to 13 C NMR, 31 P NMR takes relatively shorter time for the analysis. [113,114] Phosphitylation of lignin using 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane (TMDP) is commonly being done to quantify the hydroxyl groups, [113,114] as shown below in Figure 3c. The phosphitylated hydroxyl products are quantified using cyclohexanol as an internal standard.…”
Section: Nmrmentioning
confidence: 99%